2017
DOI: 10.1111/phn.12370
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes training for community health workers on an American Indian reservation

Abstract: Objectives: To improve the knowledge and skills of community health workers (CHWs) on an American Indian (AI) Reservation related to the management of diabetes to allow CHWs, with no prior formal diabetes education to work more effectively with individuals in the community with diabetes. Training was provided in six "face-to-face" sessions with the CHWs using the Centers for Disease Control and Prevention CHW Training Resource on Heart Disease and Stroke. Design and Sample: This is a quality improvement pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The most widely used training method was didactics (such as lectures, case presentations, clinical case discussions, group discussions, and workshops), which were employed in 24 of the 30 studies (Balcazar et al, 2006; Boutin-Foster et al, 2008; Bustillos & Sharkey, 2015; Colleran et al, 2012; Cornell et al, 2009; Cruz et al, 2013; Ferguson et al, 2007; Han et al, 2007; Haughton et al, 2015; Josiah Willock et al, 2015; Kuhajda et al, 2006; Lautner et al, 2019; Look et al, 2008; Martinez-Bristow et al, 2006; Moleta et al, 2017; Policicchio & Dontje, 2018; Prezio et al, 2013; Pullen-Smith et al, 2008; Swider et al, 2010; Valen et al, 2012; Vaughan et al, 2020; Wagner et al, 2020; Walton et al, 2012; Woodruff et al, 2010). Another three studies used a field experience component in addition to didactic sessions (Harvey et al, 2009; Hill-Briggs et al, 2007; McCloskey, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most widely used training method was didactics (such as lectures, case presentations, clinical case discussions, group discussions, and workshops), which were employed in 24 of the 30 studies (Balcazar et al, 2006; Boutin-Foster et al, 2008; Bustillos & Sharkey, 2015; Colleran et al, 2012; Cornell et al, 2009; Cruz et al, 2013; Ferguson et al, 2007; Han et al, 2007; Haughton et al, 2015; Josiah Willock et al, 2015; Kuhajda et al, 2006; Lautner et al, 2019; Look et al, 2008; Martinez-Bristow et al, 2006; Moleta et al, 2017; Policicchio & Dontje, 2018; Prezio et al, 2013; Pullen-Smith et al, 2008; Swider et al, 2010; Valen et al, 2012; Vaughan et al, 2020; Wagner et al, 2020; Walton et al, 2012; Woodruff et al, 2010). Another three studies used a field experience component in addition to didactic sessions (Harvey et al, 2009; Hill-Briggs et al, 2007; McCloskey, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 30 articles included in the review, only nine studies used a validated instrument for assessing CHW competencies (Colleran et al, 2012; Han et al, 2007; Haughton et al, 2015; Look et al, 2008; Moleta et al, 2017; Policicchio & Dontje, 2018; Tang et al, 2011; Vaughan et al, 2020; Zurawski et al, 2016). The most common validated instrument used was the Diabetes Knowledge Test (DKT), which was utilized by six out of the nine studies (Colleran et al, 2012; Han et al, 2007; Look et al, 2008; Policicchio & Dontje, 2018; Tang et al, 2011; Vaughan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, when discussing CHWs, the diverse range of activities they undertake as a result of their location and the diseases they must target need to be taken into account [4,5]. Previous studies on CHWs have shown that developing countries often train CHWs to undertake infectious disease-and maternal and child health-related activities, whereas developed countries often train CHWs to undertake the prevention and management of non-communicable diseases (NCDs) such as heart disease, various cerebrovascular diseases, and diabetes [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%